Refractory cachexia and truth‐telling about terminal prognosis: a qualitative study. (28th December 2012) - Millar, C.; Reid, J.; Porter, S.
Refractory cachexia and truth‐telling about terminal prognosisa qualitative study The purpose of this paper is to examine the consequences that medical practitioners' decisions about whether or not to be candid about terminal prognosis have for those suffering from refractory cachexia and their families. It presents the findings of a qualitative study that used focus groups and semi‐structured interviews of a volunteer sample of doctors, nurses and dieticians in a cancer centre of a large teaching hospital in Northern Ireland. Respondents reported that some physicians tended to avoid discussing terminal prognosis in a direct manner with their patients. Nurses and dieticians tended to be reluctant to engage in conversations about weight loss with patients with cachexia. One of the reasons they reported for their lack of acknowledgement of weight loss concerned the close association between refractory cachexia and terminal prognosis. Because they viewed the telling of bad news as an exclusive prerogative of medical practitioners, they did not feel in a position to discuss cachexia because they were concerned that this had the potential to raise end‐of‐life issues that lay outside the boundaries of their professional role. This meant patients and their families were provided with little information about how to cope with the distressing consequences of cachexia.